ショウワ キチ チカク ノ カイヒョウ カ デ カンサツ サレタ Paralabidocera antarctica ドウキャク ルイ ノ シュウグン ニ ツイテ - 谷村, 篤; タニムラ, アツシ; 箕田, 嵩; ミノダ, タカシ; 福地, 光男; フクチ, ミツオ; 星合, 孝男; ホシアイ, タカオ; 大塚, 英明; オオツカ, ヒデアキ; Tanimura, Atsushi; Minoda, Takashi; et al. (1984)
P(論文) 1982年1月22日から23日にかけて, 昭和基地近くの北の瀬戸(水深約10m)の海氷下において, Paralabidocera antarctica(橈脚類)の濃密な単一群が観察された。出現した本種の大部分は成体であった。昼間, P.antarcticaは海氷下面に集群を形成し, およそ2-6×10^4個体/m^3の密度で, 海氷下面付近のきわめて狭い層に平板状に分布していたものと推定された。成体雌の大部分に精包の付着がみられ, 集群が生殖行動と関連していることが示唆された。また, 集群は海氷下面の明るさに誘引されることによって生じたものと思われた。夜間, 本種の集群は全水柱から消失した。この夜間の集群の消失は, 個体群の大部分が海氷中に入りこんだために起こった可能性があることが示唆された。 A monospecific swarm of a calanoid copepod Paralabidocera antarctica was observed under the fast ice in the Kita-no-seto Strait near Syowa Station, Antarctica. During the day on January 22 to 23,a swarm appeared just beneath the undersurface of the fast ice. It was primarily composed of adults. P. antarctica seemed to have aggregated horizontally in an extremely narrow layer against the undersurface of the sea ice with density of roughly 2-6×10^4ind./m^3. Swarming may be associated with reproduction because almost all of adult females were carrying the spermatophores. P. antarctica was probably attracted to the undersurface brightness of the sea ice. At night, a swarm disappeared from the whole water column and the zooplankton composition differed from that during the day. It was assumed that the disappearance of the swarm was due to P. antarctica's entering into the loose lower part of the fast ice. departmental bulletin paper